(untitled) (Research, Society and Development, 2021)
Health education is an educational process whose scope is to increase the population’s autonomy in preventing illness, however the current crisis caused by the COVID-19 pandemic has impacted several social segments. In this context, the dissemination of scientific information on this subject plays a major role in professional and population education. Thus, in this study, the objective was to understand the scientific production available on the CAPES Portal about health education in Brazil during the COVID-19 pandemic. Therefore, a qualitative study was performed, methodologically supported by the state-of-the-art. Out of 26 articles found, eight were selected and used in the corpus of the study. The results were analyzed using the method proposed by Bardin, making the construction of two thematic categories feasible: challenges imposed on health education; and health education strategies during the COVID-19 pandemic. The discussions signaled an increase in the challenges in health education, due to fake news, due to the low adherence of the population to preventive measures, and due to the social vulnerabilities from which many people suffer. During the pandemic, health education actions are essential to maintain people’s creative capacity along with physical, emotional, and mental health. Therefore, it is concluded that the current battle requires the continuance of the involvement of the State, professionals, and society in educational strategies in health.